Immunologic profiling in schizophrenia and rheumatoid arthritis - Eaton, William W.; Rodriguez, Katrina M.; Thomas, Mekha A.; Johnson, Jeanette; Talor, Monica V.; Dohan, Curtis; Bingham, Clifton O.; Musci, Rashelle; Roth, Kimberly; Kelly, Deanna L.; Cihakova, Daniela; Darrah, Erika (Psychiatry research, 2022)
•The negative relationship between schizophrenia and rheumatoid arthritis has puzzled researchers for more than half a century.•There have not been studies of the immunologic and genetic structure of the two disorders in matched samples of patients with the two disorders.•This study includes study of immunologic and genetic structures in samples of 40 persons with schizophrenia, 40 persons with Rheumatoid Arthritis, and 40 healthy controls.•The analyses suggests that stratification of SCZ patients by cytokine profile may enable the use of currently available cytokine-based treatment strategies. The negative relationship between schizophrenia (SCZ) and rheumatoid arthritis (RA) has been observed for 85 years, but the mechanisms driving this association are unknown. This study analyzed differences in profiles of cytokines (IL-1β, IL-Ra, IL-2, IL-4, IL-6, IL-8, IL-10, IL-12p70, IFNγ, TNFα), selected genes (HLA-DRB1, IL1RN, HP2), and antibodies related to gluten sensitivity (AGA-IgG, AGA-IgA), celiac disease (tTG), and systemic autoimmunity (ANA, anti-CCP, RF) in 40 subjects with SCZ, 40 with RA, and 40 healthy controls (HC). HLA-DRB1*04:01 alleles were enriched in persons with SCZ and RA compared with HC, and the HP2/HP2 genotype was 2-fold more prevalent in AGA/tTG-positive versus negative SCZ patients. Patients with SCZ demonstrated 52.5% positivity for any of the antibodies tested, compared to 90% of RA patients and 30% of HC. Cluster analysis of the cytokines revealed three clusters: one associated with SCZ marked by high levels of IL-1Ra, one associated with HC, and one associated with both SCZ and RA marked by elevated levels of IFNγ, TNFα, and IL-6. These analyses suggest that stratification of SCZ patients by cytokine profile may identify unique SCZ subgroups and enable the use of currently available cytokine-targeted treatment strategies.